Selenium sebagai Terapi Oftalmopati Graves Derajat Ringan - Laura Agnestasia Djunaedi; Ferdy Iskandar; Cisca Kuswidyati (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2019)
Graves ophthalmopathy (GO) is the most common extrathyroid manifestation of Graves’ disease. More than 50% of Graves’ patients will experience it, even 10% of them will suffer severe GO. The mechanism of GO is associated with complex autoimmune reaction and suspected to be associated with an imbalance levels of antioxidants and oxidants in the body. Smoking and poor control of Graves’ disease also trigger the progression of ophthalmopathy.Selenium is one of the most abundant antioxidant components in the thyroid gland. Selenium can help overcome mild GO by correcting the imbalance between oxidant and antioxidant levels in the body. Nevertheless, selenium cannot be given carelessly because improper dosing can lead to the several types of cancer as well as type 2 diabetes mellitus.